Immunosuppressive treatment of chronic periaortitis: a retrospective study of 20 patients with chronic periaortitis and a review of the literature. Issue 6 (16th May 2005) - Warnatz, K; Keskin, A G; Uhl, M; Scholz, C; Katzenwadel, A; Vaith, P; Peter, H H; Walker, U A
Abstract : Background: Retroperitoneal fibrosis (RPF) and inflammatory aneurysm of the abdominal aorta (IAAA) are regarded as two manifestations of the same disease, termed "chronic periaortitis". Objective: To determine the optimal therapeutic and diagnostic approaches to IAAA. Methods: The outcome of medical immunosuppressive and surgical treatment of 20 patients was examined. Measurements of the C reactive protein (CRP) were compared with contrast enhanced imaging studies in the follow up of the patients. Results: The diameter of the periaortic mantle and its contrast enhancement improved in 13/15 (87%) patients given immunosuppressive treatment for a period of more than 6 months. Strong contrast enhancement was associated with a substantial rise in CRP, but no correlation between the CRP value and thickness of the fibrotic mass was found, even at intraindividual follow up. Conclusions: Immunosuppressive treatment should be included in the first line treatment of patients with RPF and should be maintained long term. Imaging studies are better than CRP measurements in the evaluation of response to treatment.